Palliative Care in Healthcare Networks: Perspectives for Comprehensive and Humanized Care - Rosenilda Rodrigues dos Santos; Ana Paula Martins de Souza; Sérgio Raimundo Ernesto Machado; Oldair Donizete Galeni; Grazielli Meneses Brito; Viviane Gonçalves Ferreira; Meirielem Marina Araújo Bevilacqua; José Roberval Ferreira de Oliveira (RSV, 2026)
Palliative care has become an essential component of contemporary healthcare systems due to population ageing, the increasing prevalence of chronic diseases, and the growing need for approaches capable of addressing complex health conditions beyond curative interventions. Traditionally associated with end-of-life care, palliative care has expanded its scope to include early interventions focused on symptom control, quality of life improvement, psychosocial support, and respect for individual preferences throughout the course of serious illnesses. However, its integration into healthcare networks remains a challenge in many contexts due to organizational barriers, limited professional training, and insufficient incorporation into public health policies. This academic essay analyzes the role of palliative care within healthcare networks, emphasizing perspectives for comprehensive and humanized care. The discussion explores the principles guiding palliative approaches, the importance of multidisciplinary teamwork, the challenges associated with integrating palliative care into different levels of healthcare, and the role of public policies in expanding access. The manuscript argues that effective palliative care requires a shift from fragmented and disease-centered models toward integrated systems capable of recognizing biological, psychological, social, and existential dimensions of health.